This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x + x 1 = 2 ⇒ x 2 + x 2 1 = 2 ⇒ x n + x n 1 = 2 For all even n x 9 9 + x 9 9 1 = ( x + x 1 ) ( x 9 8 + x 9 8 1 ) − ( x + x 1 ) = 2 ⋅ 2 − 2 = 2
Why were you able to generalize x n + x n 1 ∀ even n ?
Log in to reply
In general, under the given condition x n + x n 1 = 2 ∀ integer n ... but don't know how to prove it.... I'll be thinking about
Problem Loading...
Note Loading...
Set Loading...
x + x 1 = 2
x x 2 + 1 = 2
x 2 − 2 x + 1 = 0 ⟹ x = 1
1 9 9 + 1 9 9 1 = 2